Android Application for Children Learning Malay as Second Language - Haslinda Bt Mohamaddiah, Haslinda (Universiti Teknologi PETRONAS, 2012)
With the proliferation of technology, this paper represent a framework for learning Malay language as second language for early age children using Android based. This approach is to suit the evolution of technology to make learning for children is mobile. Using this application, learning process can be done regardless of place and time. This application is to encourage children who learn Malay language as second language to learn language using technology. This application also focusing to the students in early age; might be from kindergarten to primary schools. The concept play and learn is implemented in this application to give excitement in learning language. Children also can learn by their own using this application as it is user friendly and understandable by children.